The deep imprint of Roman sandals: Evidence of long-lasting effects of Roman rule on personality , economic performance, and well-being in Germany - Michael Fritsch; Martin Obschonka; Fabian Wahl; Michael Wyrwich (Friedrich Schiller University Jena, 2020)
We investigate whether the Roman presence in the southern part of Germany nearly 2,000 years ago had a deep imprinting effect with long run consequences on a broad spectrum of measures ranging from present-day personality profiles to a number of socioeconomic outcomes and why. Today's populations living in the former Roman part of Germany score indeed higher on certain personality traits, have higher life and health satisfaction, longer life expectancy, generate more inventions and behave in a more entrepreneurial way. These findings help explain that regions under Roman rule have higher present-day levels of economic development in terms of GDP per capita. The effects hold when controlling for other potential historical influences. When addressing potential channels of a long term effect of Roman rule the data indicates that the Roman road network plays an important role as a mechanism in the imprinting that is still perceptible today.
Keywords: N9; O1; I31; 330; Romans; personality traits; culture; well-being; regional performance; Limes